1992
DOI: 10.1080/00221689209498888
|View full text |Cite
|
Sign up to set email alerts
|

Short-term local scour

Abstract: Local scour downstream of an apron with a swept-out hydraulic jump is shown to develop very rapidly, that is in less than 1% of the time to reach the ultimate scour depth. The short-term scour although not as deep as the long-term scour, occurs much closer to the apron. The limiting short-term scour depth is found to be related to flow regime or type of hydraulic jump that dominates the flow in the scour hole. The deepest shortterm scour was associated with the plunging jump (B-jump) and the adverse jump regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…A progressive stage which approaches equilibrium after a very long time (long-term scour). Mohamed and McCorquodale (1992) observed that the equilibrium depth for short-term scour established rapidly in less than 1% of the time to reach the long-term scour depth. The shortterm scour although not as deep as the long-term scour occurs much closer to the apron; the bed is more highly fluidized than in the regime that governs the long-term scour.…”
Section: IImentioning
confidence: 98%
See 1 more Smart Citation
“…A progressive stage which approaches equilibrium after a very long time (long-term scour). Mohamed and McCorquodale (1992) observed that the equilibrium depth for short-term scour established rapidly in less than 1% of the time to reach the long-term scour depth. The shortterm scour although not as deep as the long-term scour occurs much closer to the apron; the bed is more highly fluidized than in the regime that governs the long-term scour.…”
Section: IImentioning
confidence: 98%
“…A cursory evaluation of the test startup conditions in several of the studies mentioned in this chapter indicates that scour pattern is quite varied and depends on how the flow is initially commenced. For example, Kells et al (2001) had the nozzle outlet plugged, whereas Balachandar et al (2000) and Mohamed and McCorquodale (1992) had the sluice gate closed until proper head and tailwater conditions were established. Following this, the nozzle was unplugged or the sluice gate opened to a predetermined extent to generate the jet flow.…”
Section: Effect Of Test Startup Conditions On Local Scourmentioning
confidence: 99%
“…It is well known in the literature that there are two stages of local scour development (E.g. [15]): an initial quick stage followed by a progressive stage, which achieves equilibrium after a long time. This paper deals with the long-term local scour at bed sills.…”
Section: Definition Of the Problemmentioning
confidence: 99%
“…The reason for this is that the energy of the jet that formed the scour was dissipated by diving into the water bag that was formed when the tailwater level increased. Previous research has shown that the dynamics of local scour is dependent on the tailwater depth (for example; Balachandar et al, 2000;Mohamed and McCorquodale, 1992;Johnston, 1990;Chatterjee and Ghosh, 1980). Figure 9 shows that, for a stepped chute, the velocity at the end of the stilling basin increased proportional to the increase in cute angle.…”
Section: Resultsmentioning
confidence: 98%